2017
DOI: 10.1371/journal.pone.0179433
|View full text |Cite
|
Sign up to set email alerts
|

Antennal transcriptome analysis of the piercing moth Oraesia emarginata (Lepidoptera: Noctuidae)

Abstract: The piercing fruit moth Oraesia emarginata is an economically significant pest; however, our understanding of its olfactory mechanisms in infestation is limited. The present study conducted antennal transcriptome analysis of olfactory genes using real-time quantitative reverse transcription PCR analysis (RT-qPCR). We identified a total of 104 candidate chemosensory genes from several gene families, including 35 olfactory receptors (ORs), 41 odorant-binding proteins, 20 chemosensory proteins, 6 ionotropic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…These results were similar to the classifications of most insect OBPs [25,37,42]. 25,43,48 Interestingly, AdisOBP1, AdisOBP17 and AdisOBP40 did not cluster into these 4 protein subfamilies, but multiple sequence alignments of the A. dissimilis OBPs revealed that 3 of the OBPs contain no conserved cysteines. Their construction requires further to verification.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results were similar to the classifications of most insect OBPs [25,37,42]. 25,43,48 Interestingly, AdisOBP1, AdisOBP17 and AdisOBP40 did not cluster into these 4 protein subfamilies, but multiple sequence alignments of the A. dissimilis OBPs revealed that 3 of the OBPs contain no conserved cysteines. Their construction requires further to verification.…”
Section: Discussionsupporting
confidence: 78%
“…Insect OBPs are expressed in the sensory organs [22,25,37,[43][44][45]. 22,25,43,49−51 Our result showed that 23 AdisOBPs were significantly expressed in both female and male antennae compared to other tissues.…”
Section: Discussionmentioning
confidence: 72%
“…OBPs are expressed specifically in the antennae and other parts associated with olfactory organs 15 , 19 , 31 , 41 43 . Our comprehensive expression analysis revealed that 23 AdisOBPs were found to be restricted to the antenna.…”
Section: Discussionmentioning
confidence: 99%
“…All data were normalized to endogenous β-actin levels from the same individual samples. The relative fold change was assessed by comparing the expression level in male moths to that in females [ 34 ]. The results were presented as the means of the fold change in three biological duplicates.…”
Section: Methodsmentioning
confidence: 99%